Financial performance of university of Ibadan muslim staff cooperative, investments and credit society limited (2019)
Business enterprise whether for profit or not-for-profit organization must make an income that will cover its costs. Its performance will dictate its survival and growth. Therefore, the study was designed to examine the financial statements of the University of Ibadan Muslim Staff Cooperative, Investments and credit Society limited. (UIMSCICS) with a view to measuring its performance using CAMEL (Capital, Asset, Management, Efficiency and Liquidity). Common Size Statement is also used to do structural analysis of the audited financial statement of the society. The study reveals that the strength of the society is in its management and interest free loans. Its cost of sales is too high (93.7% in 2018). Its capital adequacy, total investment to total assets and net surplus are on the increase but the latter is increasing at a reducing rate. The society does not have non-performing loans. This should be maintained for it makes the quality of its assets very good. The society should find alternative ways of investing their idle funds to generate more income for its members.